Cochrane corner: NOACs in atrial fibrillation patients post-percutaneous coronary intervention - Al Said, Samer; Katus, Hugo; Alabed, Samer (Heart, 2020)
One in ten people undergoing percutaneous coronary intervention (PCI) has underlying atrial fibrillation (AF). They are often treated with long-term oral anticoagulation for stroke prevention and are commenced on antiplatelet therapy post-PCI to prevent stent thrombosis.1 A careful balance of risk of bleeding versus thrombosis is essential. - - Options for oral anticoagulation include vitamin K antagonists (VKAs), for example, warfarin, and non‐vitamin K antagonist oral anticoagulants (NOACs), also referred to as direct oral anticoagulants. In contrast to VKA, NOACs directly inhibit either thrombin (dabigatran) or factor X (rivaroxaban, apixaban and edoxaban). Recent randomised controlled trials (RCTs) have compared NOACs with warfarin in patients with AF undergoing PCI. We reviewed these RCTs to summarise their efficacy and safety results.2 One of our aims was also to compare NOACs with each other; however, no RCT conducted such a comparison. We, therefore, performed a network meta-analysis to compare NOACs indirectly. A network meta-analysis is a unique statistical technique that facilitates indirect comparisons of interventions based on a common comparator across trials, that is, warfarin, in our analysis (figure 1). - - - - Figure 1 - Network diagram for major bleeding. Nodes are weighted according to the number of studies that includes the respective intervention. Edges are weighted according to the number of patients included in the respective comparison. Numbers on the lines represent the number of trials …
Gesehen am 05.11.2020